Anti-fatigue Performance in SSVEP-Based Visual Acuity Assessment: A Comparison of Six Stimulus Paradigms - Zheng, Xiaowei; Xu, Guanghua; Zhang, Yubin; Liang, Renghao; Zhang, Kai; Du, Yuhui; Xie, Jun; Zhang, Sicong (Frontiers in Human Neuroscience, 2020)
Purpose. The occurrence of mental fatigue when users stare at stimuli is a critical problem in the implementation of steady-state visual evoked potential (SSVEP)-based visual acuity assessment, which may weaken the SSVEP amplitude and signal-to-noise ratio (SNR) and subsequently affect the results of visual acuity assessment. This study aimed to explore the anti-fatigue performance of six stimulus paradigms (reverse vertical sinusoidal gratings, reverse horizontal sinusoidal gratings, reverse vertical square-wave gratings, brief-onset vertical sinusoidal gratings, reversal checkerboards and oscillating expansion-contraction concentric-rings) in SSVEP acuity assessment. Methods. Based on four indices of α+θ index, pupil diameter, National Aeronautics and Space Administration Task Load Index (NASA-TLX), and amplitude and SNR of SSVEPs, this study quantitatively evaluated the mental fatigue in six SSVEP visual attention runs corresponding to six paradigms with twelve subjects. Results. These indices of mental fatigue showed a good agreement. Results showed the paradigm of motion expansion-contraction concentric-rings had a superior anti-fatigue efficacy than the other five paradigms of conventional onset mode or pattern reversal mode during prolonged SSVEP experiment. The paradigm of brief-onset mode showed the lowest anti-fatigue efficacy, and the other paradigms of pattern reversal SSVEP paradigms showed similar anti-fatigue efficacy, which was between motion expansion-contraction mode and onset mode. Conclusion. This study recommended the paradigm of oscillating expansion-contraction concentric-rings as the stimulation paradigm in SSVEP visual acuity because of its superior anti-fatigue efficacy.